Perte d’usage - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1981)
Some public liability policies in Canada include the words "loss of use" in the definition of Property Damage as covered by the policy. The term is vague and may be easily misinterpreted. For instance, does it include extra expenses incurred by the owner of the damaged property? Can it be extended to cover loss of profits or unexpected consequences of the loss? The term should be clarified in order to suppress all ambiguity in the application of the intended liability coverage.